Penerapan Nilai-Nilai Roma 12:2 dalam Membentuk Spiritualitas Kristen di Era Kontemporer yang Relevan dan Kontekstual - Rosmawati Rosmawati; Angelicha Tangke Tasik; Delpianti Delpianti; Gita Sartiva Parinussa; Juan Fakkach Tulak Allo (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
In the digital era, Christians face significant challenges in maintaining an authentic spirituality amidst a continuous stream of information and the influence of popular culture that often contradicts biblical values. The command in Romans 12:2 to "not conform to the pattern of this world, but be transformed by the renewing of your mind" remains highly relevant, yet its practical application in contemporary Christian life is frequently overlooked. This study aims to explore the theological depth of Romans 12:2, identify the dominant patterns of worldly thought in the digital age, and develop a contextual and applicable framework for transformative Christian spirituality. Utilizing a qualitative method with a library research approach, data were gathered from theological works, biblical commentaries, and scholarly literature on spirituality, culture, and digital engagement. The study reveals that the renewal of the mind refers not only to a personal inner change but to a reorientation of worldview through the power of the Holy Spirit. This transformation involves resisting cultural tendencies such as self-image obsession on social media, intellectual complacency caused by technological convenience, and the rise of individualistic spirituality detached from community life. To address these challenges, the study proposes several implementation strategies: fostering deeper biblical literacy contextualized to current issues, cultivating critical thinking as a form of spiritual discipline, and nurturing accountability within faith communities. These elements form a holistic framework of contemporary Christian spirituality that is Christ-centered, critically aware, and outward-focused in mission. The implications of this framework suggest that Christian spirituality in the digital era must engage both heart and mind, remain rooted in Scripture, and be lived out in communal and missional contexts.